Growth and characterization of PbO Nanorods grown using facile oxidation of lead sheet - Yousefi, Ramin; Jamali Sheini, Farid; Sa΄aedi, Abdolhossein; Cheraghizade, Mohsen (Universiti Kebangsaan Malaysia, 2015)
PbO nanorods were synthesized by oxidation of lead sheets under an oxygen ambiance with different temperatures at 330, 400, 450 and 550ºC in a tube furnace. Scanning electron microscope (SEM) results showed that the nanorods started growing on the sheet that was placed at 330ºC. On the other hand, by increasing of the temperature to 550°C more nanorods appeared on the Pb sheet, which were lied on the lead sheet. X-ray diffraction pattern (XRD) indicated that the nanorods had α-PbO structures. However, a few β-PbO phases also appeared for the nanorods. Raman measurements confirmed the XRD results and indicated two Raman active modes that belonged to α-PbO phase for the nanorods. In addition, the Raman spectrum of the nanorods showed a weak peak of the β-PbO structure. The optical properties of the products were characterized using a room temperature photoluminescence (PL) technique. The PL result indicated a band gap for the PbO nanorods in the visible region.